2017
DOI: 10.1177/1362361317701267
|View full text |Cite
|
Sign up to set email alerts
|

Age of diagnosis of autism spectrum disorder in Latino children: The case of Venezuelan children

Abstract: Latino children are diagnosed with autism spectrum disorder later in life, usually with more severe symptoms, and lower IQs, compared with non-Latino children. Possible reasons for such disparities could be due to lower levels of parent education, lower socioeconomic status, limited knowledge of parents about autism spectrum disorder, and diminished health-care knowledge. The goal of the study was to describe the age of parental concerns and at first autism spectrum disorder diagnosis, and factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
3
36
0
3
Order By: Relevance
“…Several studies reported the age at ASD diagnosis for distinct ASD subtypes. For instance, the mean age at diagnosis for autistic disorder (eight studies) ranged between 33.8 and 194 months and the median age at diagnosis (nine studies) between 30 and 68.1 months (studies for mean age: Begeer et al, 2013; Bent et al, 2015; Bravo Oro et al, 2012; Brett et al, 2016; Hall-Lande et al, 2018; Höfer et al, 2019; Montiel-Nava et al, 2017; Sicherman et al, 2017 and studies for median age: U.S. Department of Health and Human Services, 2014; Baio et al, 2018; Bent et al, 2015; Bickel et al, 2015; Brett et al, 2016; Christensen, Baio, et al, 2016; Hall-Lande et al, 2018; Hinkka-Yli-Salomäki et al, 2014; Sicherman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the age at ASD diagnosis for distinct ASD subtypes. For instance, the mean age at diagnosis for autistic disorder (eight studies) ranged between 33.8 and 194 months and the median age at diagnosis (nine studies) between 30 and 68.1 months (studies for mean age: Begeer et al, 2013; Bent et al, 2015; Bravo Oro et al, 2012; Brett et al, 2016; Hall-Lande et al, 2018; Höfer et al, 2019; Montiel-Nava et al, 2017; Sicherman et al, 2017 and studies for median age: U.S. Department of Health and Human Services, 2014; Baio et al, 2018; Bent et al, 2015; Bickel et al, 2015; Brett et al, 2016; Christensen, Baio, et al, 2016; Hall-Lande et al, 2018; Hinkka-Yli-Salomäki et al, 2014; Sicherman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To monitor developmental concerns, or to more specifically screen for autism, the development of culturally appropriate surveillance, screening and diagnostic tools is vital. Late or no diagnosis disadvantages individuals with ASD in distinct cultural or socioeconomic settings, and bars them from effective early intervention or educational support (Bakare & Munir, 2011;Bello-Mojeed, Omigbodun, Bakare, & Adewuya, 2017;Montiel-Nava, Chacín, & González-Ávila, 2017;Ruparelia et al, 2016). Moreover, little is known about the cultural and contextual adaptations required to make interventions feasible, acceptable and effective across low-resource settings (Al Maskari, Melville, & Willis, 2018;Franz, Chambers, von Isenburg, & de Vries, 2017;Guler, de Vries, Seris, Shabalala, & Franz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Montiel 19 informa sobre el único estudio de niños TEA en América Latina, que similar a lo señalado muestra que las preocupaciones de los padres aparecen tempranamente a los 17 meses, pero el diagnóstico se demora 3 años en promedio (53-54 m). Salomone 20 estudiando una muestra de 23 países europeos, compuesta por 1.410 niños menores de 7 años, encontró una edad de diagnóstico de 42 meses, con una variación considerable entre países, que va desde los 33-50 meses. Los niños con mejor capacidad verbal se identificaron más tarde, especialmente si eran mujeres, apoyando las nociones de una manifestación más sutil en mujeres y que los niños con síntomas más leves se diagnostican más tarde 7,11,[19][20][21] .…”
Section: Discussionunclassified